Survival Analysis of Patient Healing in Mental Disorders Using Kaplan Meier’s Method and Log-Rank Test - Darmawan, Rahmat; Lubis, Riri Syafitri (Universitas Wiralodra, 2023)
A mental disorder is a mental dysfunction that can interfere with everyday activities. Based on the characteristics of the area of the City of Medan there are problems with mental disorders, the high number of ODGJ cases is very dangerous for society. To this end, a survival analysis of the ODGJ patient’s lifespan time was carried out at the Karsa Medan Soul Hospital with the Kaplan-Meier test as a calculation of the estimate of the healing time and the Log-Rank test to test the differences in the survival function of the treatment time of ODGJ patients. The conclusion of the test results obtained with the help of the R Studio software program version 2022.02.1+461 was that the survival function curve in ODGJ patients had an estimate of survival functions at ODGJ from a 2-day recovery time with a value of 0.99759 to 92 days with the value of 0,00000. Based on the results of the Log-Rank test with α = 0.05, obtained the test results for gender is 4.40 ˃ 3.84, then rejected , so there is a significant difference, and the results of survival estimation on the first day of male survival opportunities of 0.9931 (99.31%) are greater than women, namely 0.9919 (99. 19%), so that male patients recover longer than female patients; then the result of the Age-based Log-rank test is 2.44 ˂ 3.84, there is no rejection , so there are no significant differences, and the results of survival estimation on the first day of survival opportunities for patients aged years is 0. 992 (99.2%) is greater than the patient aged years is 0.986 (98.6%), so that patients aged years recover faster than patients aged years; and last Log-Rank results for comorbid and non-comorbid is 27.21 ˃ 3.84, there are rejections , so there is a significant difference, and the results of survival estimation on the first day the survival chance of comorbid patients is 0.9961 (99.61%) greater than that of non-comorbid patients which is 0.9937 (99.37%), so that non-comorbid patients recover faster than comorbid patients.